2011
DOI: 10.1371/journal.pone.0022634
|View full text |Cite
|
Sign up to set email alerts
|

Parasite Transmission in Social Interacting Hosts: Monogenean Epidemics in Guppies

Abstract: BackgroundInfection incidence increases with the average number of contacts between susceptible and infected individuals. Contact rates are normally assumed to increase linearly with host density. However, social species seek out each other at low density and saturate their contact rates at high densities. Although predicting epidemic behaviour requires knowing how contact rates scale with host density, few empirical studies have investigated the effect of host density. Also, most theory assumes each host has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(63 citation statements)
references
References 40 publications
(52 reference statements)
1
61
1
Order By: Relevance
“…Predators and predator cues are certainly known to have very strong plastic effects on guppy behaviour and growth Evans et al, 2007;Gosline and Rodd, 2007;Brown et al, 2013), and these guppy traits are known to influence infection (Johnson et al, 2011;Richards et al, 2010). Thus, perhaps we would have found very different results had we exposed guppies to predators or predator cues.…”
Section: Fixed Effectsmentioning
confidence: 95%
“…Predators and predator cues are certainly known to have very strong plastic effects on guppy behaviour and growth Evans et al, 2007;Gosline and Rodd, 2007;Brown et al, 2013), and these guppy traits are known to influence infection (Johnson et al, 2011;Richards et al, 2010). Thus, perhaps we would have found very different results had we exposed guppies to predators or predator cues.…”
Section: Fixed Effectsmentioning
confidence: 95%
“…Differences in predation level, on the other hand, are consistent both spatially and temporally and drive adaptive evolutionary responses in the host, such as shoaling (Houde 1997, Reznick et al 1997, Magurran 2005. Additionally, the rate of Gyrodactylus transmission is not density dependent, but is governed by the frequency of social contacts, i.e., shoaling (Johnson et al 2011). The consistent differences in parasite prevalence between populations that experience different predation pressure are thus more likely to be trait-than densitymediated.…”
Section: Fig 3 Change In Meanmentioning
confidence: 99%
“…The dominant guppy parasites, which include Gyrodactylus turnbulli and G. bullatarudis (hereafter Gyrodactylus) are directly transmitted ectoparasitic monogeneans that impact guppy swimming ability (Cable and Harris 2002), reproductive fitness (e.g., Kennedy et al 1987), and survival (van Oosterhout et al 2007). Shoaling is an important anti-predator behavioral trait in guppies that facilitates Gyrodactylus transmission (Richards et al 2010, Croft et al 2011, Johnson et al 2011, and females are more likely to become infected than males because of their higher shoaling tendency (Richards et al 2010, Johnson et al 2011. Notably, Johnson et al (2011) found that Gyrodactylus transmission remained high in aquaria with reduced guppy density, indicating that social interactions were more important than density in maintaining transmission rates.…”
Section: Introductionmentioning
confidence: 99%
“…however it still became threatened for diseases outbreak because the epidemic study on monogenea infection in guppy result showed that in social hosts like guppies. the frequency of social contact largely rules disease epidemics independent of host density [17].…”
Section: Resultsmentioning
confidence: 99%